Isolate some external parasites in some types of family Columbidae in the city of Baghdad: Suha Tariq Abdul-Karim al-Bayati and Amar M. A. Alamary - Abdul-Karim, Suha Tariq (The Iraqi Journal of Veterinary Medicine, 2012)
The aim of the study is to isolation and diagnose types of external parasites anddiagnosis in some family members Columbidae and seasonal distribution of theseparasites and the effect of temperature and humidity on the different infection rates are alsoexamining the relationship of sex and incidence of external parasitesStudy was conducted to detect parasitic infections in some types of foreign familyerythematosus where The results revealed that infestation of pigeons with one type of fliesPseudolynchia canariensis with total infestation rate was 3.33%, the highest infestation ratewas in March (13.04%) and the lowest infestation rate was in December (3.12%), this recordis consider a first record in Baghdad.The results revealed that the pigeons were infested with two Lice species, Columbicolacolumbae and Campanulotes bidentatus caompare in a rate 44.66%, 1.66% respectively withtotal rate 46.33%, the highest infestation rate was 68.57% in December and the lowest rate16.66% in August lowest was in August 15.38%, without any significant differencesrecorded.Diagnoses of one type of soft tick Argas persicus that taken from pigeon nests whichchecked – up with total rate was 35.71% (infestation with nymphs and adults) and the peakinfestation recorded in May 100% and the lowest was in March and July at a rate of 33.33%.The total rate for infestation of pigeon with larvae of tick was 2.33% and the highestinfestation was 8.33% in May and the lowest rate 2.43% in April.